NITROGEN SOURCE DOES NOT CHANGE THE MORPHOPHYSIOLOGICAL CHARACTERISTICS OF MAIZE ON A CLAY SOIL - MERGENER, RAFAEL ANDRÉ; SANGOI, LUIS; COELHO, ANTONIO EDUARDO (International Journal of Maize & Sorghum, 2022)
This study aimed to evaluate the effect of different nitrogen fertilizer sources and rates on the morphophysiological characteristics and nitrogen use efficiency of maize. The experiment was set in Campos Novos, Santa Catarina State, Brazil, during the 2016/2017 and 2017/2018 growing seasons. The experimental design was a randomized block with treatments arranged in split plots. Four nitrogen sources were evaluated in the main plots: conventional urea, protected urea, nitrification inhibitor-treated urea, and urease inhibitor-treated urea. Four nitrogen rates were assessed in the split plots: 0 (control), 140, 280, and 420 kg N ha−1. Nitrogen source did not affect ear height, leaf area index, stem diameter, or number of senescent leaves. Increments in nitrogen rate increased plant height, ear height, stem diameter, and grain nitrogen content but decreased nitrogen use efficiency. Stabilized (nitrification/urease inhibitor-treated) or protected N sources did not influence morphophysiological characteristics or improve nitrogen use efficiency of maize compared with conventional urea.